Praktik Penagihan Diskriminatif dalam Pinjaman Online: Analisis Hukum terhadap Implementasi Perlindungan Konsumen di Indonesia - Mufidah, Putri; Najwa Zulfa, Alya; Intaniassifa; Arta Rea Ahmad, An Nazwa (Forschungsforum Law Journal, 2025)
The rapid pace of technology has brought about significant changes in the economic sector, including the emergence of online lending services that provide easy access to funds. However, behind this convenience, there are serious problems related to discriminatory collection practices by online loan providers, especially those operating illegally. These practices include various forms of violations such as intimidation and threats against borrowers, gender-based harassment, unauthorized dissemination of personal data, and harsh treatment based on social status. The impact of this practice is far-reaching, causing not only financial loss but also severe psychological distress to the borrower, even leading in some cases to extreme measures such as suicide. This research aims to analyze the form of discriminatory billing practices in online lending services in Indonesia and evaluate the implementation of legal protection for consumers who are victims of such practices. Using the normative juridical research method, this research examines various relevant laws and regulations, including Law No. 8/1999 on Consumer protection, Law No. 11/2008 on Electronic Information and Transactions, as well as regulations from the Financial Services Authority (OJK) and the Indonesian Joint Funding Fintech Association (AFPI). The results show that although regulations have been implemented to protect consumers discriminatory billing practices are still rampant due to weak supervision and low public financial literacy regarding the risks of online lending. As a solution, this study recommends strengthening regulations and stricter supervision mechanisms, increasing financial education for the public, and increasing cooperation between the government and related parties in combating illegal online loans. Thus, it is hoped that consumer protection can be optimized and discriminatory billing cases can be minimized in the future.